Diffusion of small-scale pumped irrigation technologies and their association with farmer-led irrigation development in Malawi. Issue 3 (3rd April 2021) - Kamwamba-Mtethiwa, Jean; Wiyo, Kenneth; Knox, Jerry; Weatherhead, Keith
ABSTRACT: The adoption of small-scale pumped irrigation technologies was evaluated using field surveys in Malawi. Four pumped systems were identified, distinguished by ownership (group versus individual) and technology (treadle versus motorized). Farmer access to pumps was either through organizational support (incentivized) or privately (self-motivated), with progression depending on the mode of access and farmers' attributes. Self-motivated farmers had better socioeconomic status and access to knowledge supporting the pumps' continued use. Conversely, incentives drive the uptake of other pumps, and the provision of continued external support reinforced their continued use. Farmers need to be supported beyond affordability by safeguarding the availability and maintenance of pumps.